Farmers’ Demand for Climate Information Services: A Systematic Review - Ouedraogo, Adama; Egyir, Irene S; Ouedraogo, Mathieu; Jatoe, John Baptist D (MDPI, 2022)
The importance of climate information services (CIS) for farm decision-making is known worldwide. Its use is widely recommended by academics, governments, and development partners, especially in Africa. However, the supply of commercial CIS in Africa remains very low. Considering that the commercial CIS suppliers are business-oriented, the lack of supply is mainly due to the lack of evidence on the demand for it. The specific objectives of the review were to assess the demand for CIS, the key characteristics of the demanded CIS. and the key drivers for the demand for CIS in the Economic Community of West African States (ECOWAS). Through a systematic review, 123 articles were identified on the SCOPUS and Google Scholar databases and 52 papers were included in the study. The models of assessment done by the majority of authors were a simple description based on needs assessments and econometrics modelling to identify the key drivers. The results show that 68% of the farmers in ECOWAS demanded CIS. The average willingness to pay for CIS is estimated to be USD 2.01 for daily forecasts. The usability of CIS, daily forecasts and geolocalized CIS, and customized CIS are the key characteristics farmers are looking for in the ECOWAS region. The main drivers of CIS demand are price, income, vulnerability to climate variability, beliefs and religion, complementary services, gender, type of crops, and farm size. According to the consumer theory, information such as elasticity of price and income, ranked substitutes of CIS, which are still lacking, are key for understanding the CIS demand. However, the review showed that little research work has been conducted in this area. The review also shows the importance of determining among which type of goods CIS should be classified. Knowing whether CIS is a necessity good is vital for suppliers’ decision-making.